The Toxicology Investigators Consortium 2024 Annual Report - Kim Aldy; Shao Li; Mari Costantini; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; Michael Abesamis; Faiz Ahmed; Salman Ahsan; Peter Akpunonu; Adam Algren; et al. (Journal of Medical Toxicology, 2026)

Changing Interactions Between Trace Gas Fluxes, Belowground Chemistry, and Plant Traits Across an Arctic Thermokarst Landscape - Sean Fettrow; Verity Salmon; Joanne Childs; Benjamin Sulman; David Graham; Colleen M. Iversen; Elizabeth Herndon (Global Change Biology, 2025)
Arctic permafrost soils are increasingly subject to thermokarst that is, abrupt ground subsidence caused by thaw. Wetlands can form within these depressions, leading to changes in organic matter decomposition and gas fluxes (CO 2 , CH 4 , N 2 O, NH 3 ). Thermokarst wetlands tend to be dominated by graminoids, while surrounding upland tussock tundra tends to be dominated by mixed communities of shrubs and graminoids. To investigate how thermokarst alters the land‐atmosphere exchange of C and N gases in Arctic tundra, we analyzed soil, porewater, above‐ and belowground biomass, and measured gas fluxes across dominant plant functional types (PFTs) within a lowland thermokarst wetland and adjacent upland tussock tundra. Both locations were overall sinks of CO 2 , sources of CH 4 , and sources of both N 2 O and NH 3 . We found that thermokarst wetlands emitted enough CH 4 to generate a positive radiative forcing in CO 2 equivalents (+1.2 μmol m −2 s −1 CO 2 ‐eq), counteracting the high CO 2 uptake. In contrast, the upland tussock tundra had a net negative radiative forcing (−1.2 μmol m −2 s −1 CO 2 ‐eq). Differences in gas flux and soil chemistry between upland and lowland are primarily driven by flooded conditions present in thermokarst wetland. Additionally, root biomass from graminoids across both lowlands and uplands significantly correlated with CH 4 fluxes, supporting previous observations of plant‐mediated transport of CH 4 . Graminoid cover was correlated with increases in low molecular weight dissolved organic carbon, possibly associated with root exudates that fuel methanogenesis. Forb cover in the upland tussock tundra was significantly correlated with nine soil chemical variables, indicating that forbs may influence local soil chemistry or conversely, that soil chemistry controls where forbs grow. Overall, our findings indicate the variability in gas fluxes in the upland tussock tundra is partially controlled by PFT cover, while thermokarst wetlands emit enough CH 4 to counteract CO 2 uptake, with implications for carbon budget changes in Arctic systems.

Genealogical Analysis of Replicate Flower Colour Hybrid Zones in Antirrhinum - Arka Pal; Daria Shipilina; Alan Le Moan; Adrian J. McNairn; Jennifer K. Grenier; Marek Kucka; Graham Coop; Yingguang Frank Chan; Nicholas H. Barton; David L. Field; Sean Stankowski (Molecular Ecology, 2025)
A major goal of speciation research is identifying loci that underpin barriers to gene flow. Population genomics takes a ‘bottom‐up’ approach, scanning the genome for molecular signatures of processes that drive or maintain divergence. However, interpreting the ‘genomic landscape’ of speciation is complicated, because genome scans conflate multiple processes, most of which are not informative about gene flow. However, studying replicated population contrasts, including multiple incidences of secondary contact, can strengthen inferences. In this paper, we use linked‐read sequencing (haplotagging), F ST scans and genealogical methods to characterise the genomic landscape associated with replicate hybrid zone formation. We studied two flower colour varieties of the common snapdragon, Antirrhinum majus subspecies majus , that form secondary hybrid zones in multiple independent valleys in the Pyrenees. Consistent with past work, we found very low differentiation at one well‐studied zone (Planoles). However, at a second zone (Avellanet), we found stronger differentiation and greater heterogeneity, which we argue is due to differences in the amount of introgression following secondary contact. Topology weighting of genealogical trees identified loci where haplotype diversity was associated with the two snapdragon varieties. Two of the strongest associations were at previously identified flower colour loci: Flavia , that affects yellow pigmentation, and Rosea/Eluta , two linked loci that affect magenta pigmentation. Preliminary analysis of coalescence times provides additional evidence for selective sweeps at these loci and barriers to gene flow. Our study highlights the impact of demographic history on the differentiation landscape, emphasising the need to distinguish between historical divergence and recent introgression.

Petrogenesis and geochronology of the granulite facies gneissic suite hosting the Katanning Gold Deposit, Yilgarn Craton, Southwest Western Australia - Luke J. Heseldell; Nicholas E. Timms; Hugo K.H. Olierook; Thomas E. Smail; Chris Clark; Graham Conner; Sean Makin (Precambrian Research, 2025)

Phylogenomic and morphological evidence supports the reinstatement of the bamboo genus Clavinodum from Oligostachyum (Poaceae: Bambusoideae) - Zheng-Yang Niu; Zhi-Xian Zhang; Zhuo-Yu Cai; Yi-Hua Tong; Si-Jin Zeng; Sean W. Graham; Nian-He Xia (Molecular Phylogenetics and Evolution, 2025)

Cross-scale patterns of structure and maximum biomass in late-seral Douglas-fir-dominated rainforests - Russell D. Kramer; Stephen C. Sillett; Sean M.A. Jeronimo; Mark E. Graham; Miles E. LeFevre; Allyson L. Carroll; Robert Van Pelt (Forest Ecology and Management, 2025)

Persistent adaptations in sensorimotor interneuron circuits in the motor cortex with a history of sport-related concussion - Kara D. Hayes; Madison E.R. Khan; Kylee R. Graham; W. Richard Staines; Sean K. Meehan (Experimental Brain Research, 2025)

Testing for concordance between predicted species richness, past prioritization, and marine protected area designations in the western Indian Ocean - Tim R. McClanahan; Alan M. Friedlander; Julien Wickel; Nicholas A. J. Graham; J. Henrich Bruggemann; Mireille M. M. Guillaume; P. Chabanet; Sean Porter; Michael H. Schleyer; M. Kodia Azali; N. A. Muthiga (Conservation Biology, 2024)
Scientific advances in environmental data coverage and machine learning algorithms have improved the ability to make large‐scale predictions where data are missing. These advances allowed us to develop a spatially resolved proxy for predicting numbers of tropical nearshore marine taxa. A diverse marine environmental spatial database was used to model numbers of taxa from ∼1000 field sites, and the predictions were applied to all 7039 6.25‐km 2 reef cells in 9 ecoregions and 11 nations of the western Indian Ocean. Our proxy for total numbers of taxa was based on the positive correlation ( r 2 = 0.24) of numbers of taxa of hard corals and 5 highly diverse reef fish families. Environmental relationships indicated that the number of fish species was largely influenced by biomass, nearness to people, governance, connectivity, and productivity and that coral taxa were influenced mostly by physicochemical environmental variability. At spatial delineations of province, ecoregion, nation, and strength of spatial clustering, we compared areas of conservation priority based on our total species proxy with those identified in 3 previous priority‐setting reports and with the protected area database. Our method identified 119 locations that fit 3 numbers of taxa (hard coral, fish, and their combination) and 4 spatial delineations (nation, ecoregion, province, and reef clustering) criteria. Previous publications on priority setting identified 91 priority locations of which 6 were identified by all reports. We identified 12 locations that fit our 12 criteria and corresponded with 3 previously identified locations, 65 that aligned with at least 1 past report, and 28 that were new locations. Only 34% of the 208 marine protected areas in this province overlapped with identified locations with high numbers of predicted taxa. Differences occurred because past priorities were frequently based on unquantified perceptions of remoteness and preselected priority taxa. Our environment–species proxy and modeling approach can be considered among other important criteria for making conservation decisions.

Southern Flounder: Major Milestones and Remaining Knowledge Gaps in Their Biology, Ecology, and Fishery Management - Stephen R. Midway; Frederick S. Scharf; Michael A. Dance; Nancy J. Brown-Peterson; Joseph C. Ballenger; Nicolette S. Beeken; Russell J. Borski; Tanya L. Darden; Kenneth A. Erickson; Troy M. Farmer; Ashley Fincannon; John Godwin; et al. (Reviews in Fisheries Science & Aquaculture, 2024)

Afrothismiaceae (Dioscoreales), a new fully mycoheterotrophic family endemic to tropical Africa - Martin Cheek; Marybel Soto Gomez; Sean W. Graham; Paula J. Rudall (Kew Bulletin, 2024)
Summary Afrothismia is a genus of non-photosynthetic mycoheterotrophs from the forests of continental tropical Africa. Multiple phylogenetic inferences using molecular data recover the genus as sister to a clade comprising mycoheterotrophic Thismiaceae and the photosynthetic family Taccaceae, contrary to earlier placements of Afrothismia and Thismiaceae within Burmanniaceae. Morphological support for separating Afrothismia from the rest of Thismiaceae has depended on the zygomorphic flowers of Afrothismia (although some species of Thismia are also zygomorphic), and their clusters of root tubers, each with a terminal rootlet. The number of described species of Afrothismia has recently increased from four to 16, with seven more species as yet undescribed; these discoveries have added morphological characters that support its distinction from Thismiaceae. Most notably, the ovary in Afrothismia has a single stalked placenta, and circumscissile fruits from which seeds are exserted by placental elevation (vs in Thismiaceae, three placentas, a deliquescing fruit lid, and seeds not exserted). Afrothismia stamens are inserted in the lower part of the floral tube, where they are attached to the stigma, and individual flowers are subtended by a single large dorsal bract. In contrast, in Thismiaceae, stamens are inserted at the mouth of the tube, free of and distant from the stigma, and each flower is subtended by a loose whorl of (2 –) 3 (– 4) bracts. Here we formally characterise Afrothismiaceae and review what is known of its development, seed germination, interactions with mycorrhizal Glomeromycota, biogeography, phylogeny and pollination biology. All but one ( Afrothismia insignis ; Vulnerable) of the 13 species assessed on the IUCN Red List of Threatened Species are either Endangered or Critically Endangered; one species ( A. pachyantha ) is considered extinct.

Temporal evolution of shallow marine diagenetic environments: Insights from carbonate concretions - Sean J. Loyd; Patrick Meister; Bo Liu; Kevin Nichols; Frank A. Corsetti; Robert Raiswell; William Berelson; Graham Shields; Mark Hounslow; John W.F. Waldron; Bayne Westrick-Snapp; Jamie Hoffman (Geochimica et Cosmochimica Acta, 2023)

Six years of demography data for 11 reef coral species - Joshua S. Madin; Andrew H. Baird; Sean R. Connolly; Maria A. Dornelas; Mariana Álvarez‐Noriega; Michael J. McWilliam; Miguel Barbosa; Shane A. Blowes; Paulina Cetina‐Heredia; Alec P. Christie; Vivian R. Cumbo; Marcela Diaz; et al. (Ecology, 2023)
Scleractinian corals are colonial animals with a range of life‐history strategies, making up diverse species assemblages that define coral reefs. We tagged and tracked ~30 colonies from each of 11 species during seven trips spanning 6 years (2009–2015) to measure their vital rates and competitive interactions on the reef crest at Trimodal Reef, Lizard Island, Australia. Pairs of species were chosen from five growth forms in which one species of the pair was locally rare (R) and the other common (C). The sampled growth forms were massive ( Goniastrea pectinata [R] and G. retiformis [C]), digitate ( Acropora humilis [R] and A. cf. digitifera [C]), corymbose ( A. millepora [R] and A. nasuta [C]), tabular ( A. cytherea [R] and A. hyacinthus [C]) and arborescent ( A. robusta [R] and A. intermedia [C]). An extra corymbose species with intermediate abundance, A. spathulata was included when it became apparent that A. millepora was too rare on the reef crest, making the 11 species in total. The tagged colonies were visited each year in the weeks prior to spawning. During visits, two or more observers each took two or three photographs of each tagged colony from directly above and on the horizontal plane with a scale plate to track planar area. Dead or missing colonies were recorded and new colonies tagged to maintain ~30 colonies per species throughout the 6 years of the study. In addition to tracking tagged corals, 30 fragments were collected from neighboring untagged colonies of each species for counting numbers of eggs per polyp (fecundity); and fragments of untagged colonies were brought into the laboratory where spawned eggs were collected for biomass and energy measurements. We also conducted surveys at the study site to generate size structure data for each species in several of the years. Each tagged colony photograph was digitized by at least two people. Therefore, we could examine sources of error in planar area for both photographers and outliners. Competitive interactions were recorded for a subset of species by measuring the margins of tagged colony outlines interacting with neighboring corals. The study was abruptly ended by Tropical Cyclone Nathan (Category 4) that killed all but nine of the more than 300 tagged colonies in early 2015. Nonetheless, these data will be of use to other researchers interested in coral demography and coexistence, functional ecology, and parametrizing population, community, and ecosystem models. The data set is not copyright restricted, and users should cite this paper when using the data.

New constraints on the structure and composition of the lithospheric mantle beneath the Slave craton, NW Canada from 3-D magnetotelluric data – Origin of the Central Slave Mantle Conductor and possible evidence for lithospheric scale fluid flow - Sean P. Bettac; Martyn J. Unsworth; D. Graham Pearson; Jim Craven (Tectonophysics, 2023)

A Macroinfaunal Ecosystem Engineer May Facilitate Recovery of Benthic Invertebrates and Accompanying Ecosystem Services After an Oil Spill - John W. Fleeger; David S. Johnson; Scott A. Zengel; Irving A. Mendelssohn; Donald R. Deis; Sean A. Graham (Estuaries and Coasts, 2022)

Genetic analyses of gynecological disease identify genetic relationships between uterine fibroids and endometrial cancer, and a novel endometrial cancer genetic risk region at the WNT4 1p36.12 locus - Pik Fang Kho; Sally Mortlock; Frederic Amant; Daniela Annibali; Katie Ashton; John Attia; Paul L. Auer; Matthias W. Beckmann; Amanda Black; Louise Brinton; Daniel D. Buchanan; Stephen J. Chanock; et al. (Human Genetics, 2021)

Sharing and reporting benefits from biodiversity research - Emily Marden; Richard J. Abbott; Frédéric Austerlitz; Daniel Ortiz‐Barrientos; Regina S. Baucom; Pim Bongaerts; Aurélie Bonin; Camille Bonneaud; Luke Browne; C. Alex Buerkle; Ana L. Caicedo; David W. Coltman; et al. (Molecular Ecology, 2021)

A morphologically cryptic salamander reveals additional hidden diversity: evidence for ancient genetic divergence in Webster’s salamander, Plethodon websteri - Sheena Feist; Thomas Mann; Sean Graham; Jessica Wooten; Cory Toyota; Debora Mann; Madeline Balius; Jose Polanco; Peyton Wolwehender; Je’Coiya Moore (Conservation Genetics, 2019)

Winged bean (Psophocarpus tetragonolobus (L.) DC.) for food and nutritional security: synthesis of past research and future direction - Alberto Stefano Tanzi; Graham Ewen Eagleton; Wai Kuan Ho; Quin Nee Wong; Sean Mayes; Festo Massawe (Planta, 2019)

Real-Time Monitoring with a Tablet App Improves Implementation of Treatments to Enhance Forest Structural Diversity - Colin T Maher; Emily Oja; Abigail Marshall; Matthew Cunningham; Lucas Townsend; Graham Worley-Hood; Luke Ruffner Robinson; Taylor Margot; Drew Lyons; Stuart Fety; Eryn E Schneider; Sean M A Jeronimo; et al. (Journal of Forestry, 2019)

Interaction between invasive plant leaf litter and NaCl on two model amphibians - Devin G. DiGiacopo; George A. Meindl; Sean Ryan; Jared Jaeger; Matthew Wersebe; Amelia Martin; Seth A. Robinson; Gabrielle Graham; Adam R. Palmer; Amanda Setteducate; Ian Murray; Kirsten Prior; et al. (Biological Invasions, 2019)

Presence of an invasive species reverses latitudinal clines of multiple traits in a native species - Christopher J. Thawley; Mark Goldy‐Brown; Gail L. McCormick; Sean P. Graham; Tracy Langkilde (Global Change Biology, 2019)
Understanding the processes driving formation and maintenance of latitudinal clines has become increasingly important in light of accelerating global change. Many studies have focused on the role of abiotic factors, especially temperature, in generating clines, but biotic factors, including the introduction of non‐native species, may also drive clinal variation. We assessed the impact of invasion by predatory fire ants on latitudinal clines in multiple fitness‐relevant traits—morphology, physiological stress responsiveness, and antipredator behavior—in a native fence lizard. In areas invaded by fire ants, a latitudinal cline in morphology is opposite both the cline found in museum specimens from historical populations across the species’ full latitudinal range and that found in current populations uninvaded by fire ants. Similarly, clines in stress‐relevant hormone response to a stressor and in antipredator behavior differ significantly between the portions of the fence lizard range invaded and uninvaded by fire ants. Changes in these traits within fire ant‐invaded areas are adaptive and together support increased and more effective antipredator behavior that allows escape from attacks by this invasive predator. However, these changes may mismatch lizards to the environments under which they historically evolved. This research shows that novel biotic pressures can alter latitudinal clines in multiple traits within a single species on ecological timescales. As global change intensifies, a greater understanding of novel abiotic and biotic pressures and how affected organisms adapt to them across space and time will be central to predicting and managing our changing environment.

Future Research Directions on the “Elusive” White Shark - Charlie Huveneers; Kirin Apps; Edgar E. Becerril-García; Barry Bruce; Paul A. Butcher; Aaron B. Carlisle; Taylor K. Chapple; Heather M. Christiansen; Geremy Cliff; Tobey H. Curtis; Toby S. Daly-Engel; Heidi Dewar; et al. (Frontiers in Marine Science, 2018)

Wetland Plant Community Responses to the Interactive Effects of Simulated Nutrient and Sediment Loading: Implications for Coastal Restoration Using Mississippi River Diversions - Sareh Poormahdi; Sean A. Graham; Irving A. Mendelssohn (Estuaries and Coasts, 2018)

Denial of long‐term issues with agriculture on tropical peatlands will have devastating consequences - Lahiru S. Wijedasa; Jyrki Jauhiainen; Mari Könönen; Maija Lampela; Harri Vasander; Marie‐Claire Leblanc; Stephanie Evers; Thomas E. L. Smith; Catherine M. Yule; Helena Varkkey; Massimo Lupascu; Faizal Parish; et al. (Global Change Biology, 2017)

Age-dependent differential expression of death-associated protein 6 (Daxx) in various peripheral tissues and different brain regions of C57BL/6 male mice - Mélissa Lessard-Beaudoin; Mélissa Laroche; Marie-Josée Demers; Catherine Duclos; Jean-Bernard Denault; Guillaume Grenier; Sean-Patrick Riechers; Erich E. Wanker; Rona K. Graham (Biogerontology, 2016)

Risk of colorectal cancer for people with a mutation in both a MUTYH and a DNA mismatch repair gene - Aung Ko Win; Jeanette C. Reece; Daniel D. Buchanan; Mark Clendenning; Joanne P. Young; Sean P. Cleary; Hyeja Kim; Michelle Cotterchio; James G. Dowty; Robert J. MacInnis; Katherine M. Tucker; Ingrid M. Winship; et al. (Familial Cancer, 2015)

Ancient Gondwana break‐up explains the distribution of the mycoheterotrophic family Corsiaceae (Liliales) - Constantijn B. Mennes; Vivienne K. Y. Lam; Paula J. Rudall; Stephanie P. Lyon; Sean W. Graham; Erik F. Smets; Vincent S. F. T. Merckx (Journal of Biogeography, 2015)
Aim Many plant families have a disjunct distribution across the southern Pacific Ocean, including the mycoheterotrophic family Corsiaceae, which provides a prime example of this biogeographical pattern. A better grasp of the family's evolutionary relationships is needed to understand its historical biogeography. We therefore aimed to (1) test the uncertain monophyly of Corsiaceae, (2) define its phylogenetic position, and (3) estimate divergence times for the family, allowing us to assess whether the distribution of the family is the result of vicariance. Location Southern South America and Australasia. Methods We analysed various combinations of mitochondrial and nuclear data to address the monophyly, phylogenetic position and age of Corsiaceae. To test its monophyly, we used a three‐locus data set including most monocot orders, and to infer its exact phylogenetic position, we used a five‐locus extended data set. We corroborated these findings using an independent plastome dataset. We then used a two‐locus dataset with taxa from all monocot orders, and a three‐locus dataset containing only taxa of Liliales, to estimate divergence times using a fossil‐calibrated uncorrelated lognormal relaxed‐clock approach. Results Corsiaceae is a monophyletic family and the sister group of Campynemataceae. This clade is the sister group of all other Liliales. The crown age of Corsiaceae is estimated to be 53 Ma (95% confidence interval 30–76 Ma). Main conclusions Corsiaceae is an ancient family of mycoheterotrophic plants, whose crown age overlaps with the plate‐tectonic split of Gondwana, consistent with a vicariance‐based explanation for its current distribution.

Candidate locus analysis of the TERT–CLPTM1L cancer risk region on chromosome 5p15 identifies multiple independent variants associated with endometrial cancer risk - Luis G. Carvajal-Carmona; Tracy A. O’Mara; Jodie N. Painter; Felicity A. Lose; Joe Dennis; Kyriaki Michailidou; Jonathan P. Tyrer; Shahana Ahmed; Kaltin Ferguson; Catherine S. Healey; Karen Pooley; Jonathan Beesley; et al. (Human Genetics, 2015)

Impact of minocycline on cerebrospinal fluid markers of oxidative stress, neuronal injury, and inflammation in HIV-seropositive individuals with cognitive impairment - Ned Sacktor; Sachiko Miyahara; Scott Evans; Giovanni Schifitto; Bruce Cohen; Norman Haughey; Julia L. Drewes; David Graham; M.Christine Zink; Caroline Anderson; Avindra Nath; Carlos A. Pardo; et al. (Journal of NeuroVirology, 2014)

Coastal wetland stability maintained through counterbalancing accretionary responses to chronic nutrient enrichment - Sean A. Graham; Irving A. Mendelssohn (Ecology, 2014)
The link between anthropogenically modified nutrient loading and coastal wetland stability is not well understood due to limited data from long‐term experiments and inconsistent findings from investigations thus far. In this study, we present results from a 13‐year oligohaline marsh fertilization experiment aimed at determining whether eutrophic conditions compromise ecosystem stability, defined here as the capacity to keep pace with sea level rise and resist the erosive forces of high‐energy meteorologic events. To accomplish this objective, we measured soil surface elevation change and soil shear strength, along with a suite of regulatory processes that included belowground standing crop, belowground decomposition, organic and mineral matter accumulation, soil accretion, and shallow subsidence. Our results identified an apparent compensatory effect of nutrient enrichment on accretionary processes whereby shallow subsidence, attributed to reduced live root standing crop, was balanced by enhanced accretion resulting from greater organic matter accumulation at the soil surface. Consequently, the rate of marsh elevation change measured over a five‐year period was unaffected after more than a decade of experimental nutrient enrichment. Furthermore, the structural integrity of the soil matrix did not deteriorate under elevated nutrient conditions; decomposition rates were similar to control plots, and although live root standing crop was reduced, the root system was evidently stronger, as soil strength tended to increase rather than decrease after nutrients were provided for 13 years. Our data suggest that enhanced nutrient loading is an unlikely destabilizing mechanism in this coastal marsh and possibly others. However, additional long‐term research will be required in a diverse range of habitats and environmental settings before broad‐based, general conclusions concerning the effects of nutrient enrichment on coastal wetland stability can be made with a high degree of certainty.

The stress of scramble: sex differences in behavior and physiological stress response in a time-constrained mating system - Lindsey Swierk; Sean P. Graham; Tracy Langkilde (Behavioral Ecology and Sociobiology, 2014)

Understanding the spectacular failure of DNA barcoding in willows ( Salix ): Does this result from a trans‐specific selective sweep? - Diana M. Percy; George W. Argus; Quentin C. Cronk; Aron J. Fazekas; Prasad R. Kesanakurti; Kevin S. Burgess; Brian C. Husband; Steven G. Newmaster; Spencer C.H. Barrett; Sean W. Graham (Molecular Ecology, 2014)
Willows ( Salix : Salicaceae) form a major ecological component of Holarctic floras and consequently are an obvious target for a DNA ‐based identification system. We surveyed two to seven plastid genome regions (~3.8 kb; ~3% of the genome) from 71 Salix species across all five subgenera, to assess their performance as DNA barcode markers. Although Salix has a relatively high level of interspecific hybridization, this may not sufficiently explain the near complete failure of barcoding that we observed: only one species had a unique barcode. We recovered 39 unique haplotypes, from more than 500 specimens, that could be partitioned into six major haplotype groups. A unique variant of group I (haplotype 1*) was shared by 53 species in three of five Salix subgenera. This unusual pattern of haplotype sharing across infrageneric taxa is suggestive of either a massive nonrandom coalescence failure (incomplete lineage sorting), or of repeated plastid capture events, possibly including a historical selective sweep of haplotype 1* across taxonomic sections. The former is unlikely as molecular dating indicates that haplotype 1* originated recently and is nested in the oldest major haplotype group in the genus. Further, we detected significant non‐neutrality in the frequency spectrum of mutations in group I, but not outside group I, and demonstrated a striking absence of geographical (isolation by distance) effects in the haplotype distributions of this group. The most likely explanation for the patterns we observed involves recent repeated plastid capture events, aided by widespread hybridization and long‐range seed dispersal, but primarily propelled by one or more trans‐species selective sweeps.

The unbearable fuzziness of being sustainable: an integrated, fuzzy logic-based aquifer health index - Sean W. Fleming; Cecilia Wong; Gwyn Graham (Hydrological Sciences Journal, 2014)

Evidence for multiple stressor interactions and effects on coral reefs - Stephen S. Ban; Nicholas A. J. Graham; Sean R. Connolly (Global Change Biology, 2014)
Concern is growing about the potential effects of interacting multiple stressors, especially as the global climate changes. We provide a comprehensive review of multiple stressor interactions in coral reef ecosystems, which are widely considered to be one of the most sensitive ecosystems to global change. First, we synthesized coral reef studies that examined interactions of two or more stressors, highlighting stressor interactions (where one stressor directly influences another) and potentially synergistic effects on response variables (where two stressors interact to produce an effect that is greater than purely additive). For stressor‐stressor interactions, we found 176 studies that examined at least 2 of the 13 stressors of interest. Applying network analysis to analyze relationships between stressors, we found that pathogens were exacerbated by more costressors than any other stressor, with ca. 78% of studies reporting an enhancing effect by another stressor. Sedimentation, storms, and water temperature directly affected the largest number of other stressors. Pathogens, nutrients, and crown‐of‐thorns starfish were the most‐influenced stressors. We found 187 studies that examined the effects of two or more stressors on a third dependent variable. The interaction of irradiance and temperature on corals has been the subject of more research (62 studies, 33% of the total) than any other combination of stressors, with many studies reporting a synergistic effect on coral symbiont photosynthetic performance ( n = 19). Second, we performed a quantitative meta‐analysis of existing literature on this most‐studied interaction (irradiance and temperature). We found that the mean effect size of combined treatments was statistically indistinguishable from a purely additive interaction, although it should be noted that the sample size was relatively small ( n = 26). Overall, although in aggregate a large body of literature examines stressor effects on coral reefs and coral organisms, considerable gaps remain for numerous stressor interactions and effects, and insufficient quantitative evidence exists to suggest that the prevailing type of stressor interaction is synergistic.

Effects of delayed settlement on post-settlement growth and survival of scleractinian coral larvae - Erin M. Graham; Andrew H. Baird; Bette L. Willis; Sean R. Connolly (Oecologia, 2013)

Effects of the serotonergic agonist mCPP on male rats in the quinpirole sensitization model of obsessive–compulsive disorder (OCD) - Mark C. Tucci; Anna Dvorkin-Gheva; Dawn Graham; Sean Amodeo; Paul Cheon; Ashley Kirk; John Peel; Leena Taji; Henry Szechtman (Psychopharmacology, 2013)

A road map for molecular ecology - Rose L. Andrew; Louis Bernatchez; Aurélie Bonin; C. Alex. Buerkle; Bryan C. Carstens; Brent C. Emerson; Dany Garant; Tatiana Giraud; Nolan C. Kane; Sean M. Rogers; Jon Slate; Harry Smith; et al. (Molecular Ecology, 2013)
The discipline of molecular ecology has undergone enormous changes since the journal bearing its name was launched approximately two decades ago. The field has seen great strides in analytical methods development, made groundbreaking discoveries and experienced a revolution in genotyping technology. Here, we provide brief perspectives on the main subdisciplines of molecular ecology, describe key questions and goals, discuss common challenges, predict future research directions and suggest research priorities for the next 20 years.

Pacific Rim Forestry / Silviculture and Forest Ecology - Vishal Singh Negi; Archana Pal; Ratnesh Singh; Dulal Borthakur; Archana Pala; Vishal Singh Negi; Dulal Borthakur; Isabel Rushanaedy; Tyler Jones; Nicklos Dudley; Dulal Borthakur; Jannai Yafuso; et al. (Journal of Forestry, 2011)
Leucaena leucocephala (leucaena) is an important agroforestry tree of tropics and subtropics due to its protein rich foliages, ability to grow on poor soils, and high level of tolerance to various stresses including drought and diseases. We hypothesized that leucaena have a unique set of genes which confer tolerance to various abiotic and biotic stresses and these genes are either absent or not expressed in other legumes that are susceptible to these stress conditions. Interspecies suppression subtractive hybridization (iSSH) was performed to identify some unique genes from leucaena using cDNAs from leucaena and Acacia confusa (acacia) as the tester and driver, respectively. We identified 100 leucaena genes showing homology to various plant genes with known functions, of which 23 genes had homology to various stress-related proteins including chitinase, PR-10 protein, wound-stress protein, type-2 metallothionein, thaumatin-like protein, disease resistance response protein, cysteine proteinase, and kunitz trypsin inhibitor. We also identified 50 leucaena genes which either had homology to hypothetical proteins (HyPs) or had no homology at all. Putative functions of 15 HyPs were predicted using conserved domain and PSI-BLAST analyses. Linear motif analyses identified 17 HyPs with MAPK recognition motif, which is involved in signaling pathways, including stress responses. This study identified 23 known and some putative unique stress-related genes from leucaena which may serve as a useful source of stress-tolerance genes for tree and crop improvement in the future.

Spatial patterns of plant diversity below‐ground as revealed by DNA barcoding - PRASAD R. KESANAKURTI; ARON J. FAZEKAS; KEVIN S. BURGESS; DIANA M. PERCY; STEVEN G. NEWMASTER; SEAN W. GRAHAM; SPENCER C. H. BARRETT; MEHRDAD HAJIBABAEI; BRIAN C. HUSBAND (Molecular Ecology, 2011)
Our understanding of the spatial organization of root diversity in plant communities and of the mechanisms of community assembly has been limited by our ability to identify plants based on root tissue, especially in diverse communities. Here, we test the effectiveness of the plastid gene rbcL , a core plant DNA barcoding marker, for investigating spatial patterns of root diversity, and relate observed patterns to above‐ground community structure. We collected 3800 root fragments from four randomly positioned, 1‐m‐deep soil profiles (two vertical transects per plot), located in an old‐field community in southern Ontario, Canada, and extracted and sequenced DNA from 1531 subsampled fragments. We identified species by comparing sequences with a DNA barcode reference library developed previously for the local flora. Nearly 85% of sampled root fragments were successfully sequenced and identified as belonging to 29 plant species or species groups. Root abundance and species richness varied in horizontal space and were negatively correlated with soil depth. The relative abundance of taxa below‐ground was correlated with their frequency above‐ground ( r = 0.73, P = 0.0001), but several species detected in root tissue were not observed in above‐ground quadrats. Multivariate analyses indicated that diversity was highly structured below‐ground, and associated with depth, root morphology, soil chemistry and soil texture, whereas little structure was evident above‐ground. Furthermore, analyses of species co‐occurrence indicates strong species segregation overall but random co‐occurrence among confamilials. Our results provide insights into the role of environmental filtering and competitive interactions in the organization of plant diversity below‐ground, and also demonstrate the utility of barcoding for the identification of plant roots.

Climate‐related, decadal‐scale assemblage changes of seagrass‐associated fishes in the northern Gulf of Mexico - F. JOEL FODRIE; KENNETH L. HECK; SEAN P. POWERS; WILLIAM M. GRAHAM; KELLY L. ROBINSON (Global Change Biology, 2010)
Global temperatures are rising, and are expected to produce a poleward shift in the distribution of many organisms. We quantified changes in fish assemblages within seagrass meadows of the northern Gulf of Mexico (GOM) between the 1970s and 2006–2007, and observed changes consistent with this forecast. During 2006–2007 we sampled seagrass meadows using the same gears and methods previously employed by R. J. Livingston in coastal waters of northwest Florida throughout the 1970s. Comparisons between datasets revealed numerous additions to the fish fauna during 2006–2007 that were completely absent in the 1970s, including: Lutjanus synagris (lane snapper), Epinephelus morio (red grouper), Chaetodon ocellatus (spotfin butterflyfish), Mycteroperca sp (grouper, non gag), Centropristis philadelphica (rock sea bass), Fistularia tabacaria (bluespotted cornetfish), Ocyurus chrysurus (yellowtail snapper), Thalassoma bifasciatum (bluehead wrasse), Abudefduf saxatilis (sergeant major), Acanthuridae spp. (surgeonfishes) and Sparisoma viride (stoplight parrotfish). Several other species showed large increases in abundance during the interval between 1979 and 2006, including Mycteroperca microlepis (gag grouper, up ∼200 ×), Lutjanus griseus (gray snapper, up ∼105 ×), and Nicholsina usta (emerald parrotfish, up ∼22 ×). All of these are tropical or subtropical species that now make up a greater percentage of seagrass‐associated fish assemblages in the northern GOM than in the past. Additionally, we observed regional increases in air and sea surface temperatures (> 3 °C) during the ∼30 years that separate Livingston's samples and ours that correlate with northern shifts in the distribution of warm‐water fishes. Documenting these range shifts is a critical first step in investigating the consequences of global warming for endemic marine communities and fishery production in the northern GOM.

Forms and accumulation of soil P in natural and recently restored peatlands—Upper Klamath Lake, Oregon, USA - Sean A. Graham; Christopher B. Craft; Paul V. McCormick; Allison Aldous (Wetlands, 2005)

Quick on the Uptake: Characterization of a Family of Plant Auxin Influx Carriers - Geraint Parry; Alan Marchant; Sean May; Ranjan Swarup; Kamal Swarup; Nick James; Neil Graham; Trudie Allen; Tony Martucci; Antony Yemm; Richard Napier; Ken Manning; et al. (Journal of Plant Growth Regulation, 2001)

Diversity of alpha and beta subunits of T-cell receptors specific for the H4 minor histocompatibility antigen - Sean L. Johnston; Donna Graham; P. J. Wettstein (Immunogenetics, 1997)